Recurrent moderate‐risk mutations in Finnish breast and ovarian cancer patients. Issue 10 (25th April 2019) - Nurmi, Anna; Muranen, Taru A.; Pelttari, Liisa M.; Kiiski, Johanna I.; Heikkinen, Tuomas; Lehto, Sini; Kallioniemi, Anne; Schleutker, Johanna; Bützow, Ralf; Blomqvist, Carl; Aittomäki, Kristiina; Nevanlinna, Heli
Abstract : Mutations in BRCA1 and BRCA2 genes predispose to breast and ovarian cancer (BC/OC) with a high lifetime risk, whereas mutations in PALB2, CHEK2, ATM, FANCM, RAD51C and RAD51D genes cause a moderately elevated risk. In the Finnish population, recurrent mutations have been identified in all of these genes, the latest being CHEK2 c.319+2T>A and c.444+1G>A. By genotyping 3, 156 cases and 2, 089 controls, we estimated the frequencies of CHEK2 c.319+2T>A and c.444+1G>A in Finnish BC patients. CHEK2 c.319+2T>A was detected in 0.7% of the patients, and it was associated with a high risk of BC in the unselected patient group (OR = 5.40 [95% CI 1.58–18.45], p = 0.007) and similarly in the familial patient group. CHEK2 c.444+1G>A was identified in 0.1% of all patients. Additionally, we evaluated the combined prevalence of recurrent moderate‐risk gene mutations in 2, 487 BC patients, 556 OC patients and 261 BRCA1/2 carriers from 109 families. The overall frequency of the mutations was 13.3% in 1, 141 BRCA1/2 ‐negative familial BC patients, 7.5% in 1, 727 unselected BC patients and 7.2% in 556 unselected OC patients. At least one moderate‐risk gene mutation was found in 12.5% of BRCA1 families and 7.1% of BRCA1 index patients, as well as in 17.0% of BRCA2 families and 11.3% of BRCA2 index patients, and the mutations were associated with an additional risk in the BRCA1/2 index patients (OR = 2.63 [1.15–5.48], p = 0.011). These results support gene panel testing of even multiple members of BC families where several mutations may segregate in different individuals. Abstract : What's new? In the Finnish population, a small number of recurrent mutations account for the majority of deleterious variations in breast and ovarian cancer susceptibility genes. The authors investigated 12 recurrent moderate‐risk mutations in Finnish breast and ovarian cancer patients. These mutations were found with similar frequency in unselected patients and BRCA1/2 ‐positive familial index patients, twice as often as in population controls. In addition, a novel association was identified between breast cancer risk and CHEK2 variant c.319+2T>A. The findings highlight the relevance of gene panel testing for breast and ovarian cancer risk assessment and its potential use for assessing breast cancer families with members who may carry different mutations.